Penetrating Wooden Injury : Wooden Stick - Siregar, Rais; Dharmajaya, Ridha; Mahyudanil (Asian Australasian Neuro and Health Science Journal (AANHS-J), 2019)
Background : Accidental penetrating brain injury is relatively uncommon representing about 0.4% of all head injuries. Penetrating brain injury (PBI) were divided into Missile and Non missile penetrating head injuries (NPHIs). Non missile penetrating head injuries (NPHIs) are relatively rare compared with missile injuries. Wooden Penetrating Brain Injury is one of Non missile penetrating head injuries (NPHIs) Case Report : 20-year-old male presented with Decreased of Conciousness. History revealed that he was riding motorcycle and had an crash injury with other motorcycle rider from a head. He fell down and a broken wooden stick entered into his skull. Airway was clear, Breathing was spontan and respiratory rate 26 per minutes, Circulatory finding were warm skin, pulse rate of 118 per minute and blood pressure of 140/80 mm Hg, Glasgow Coma Scale (GCS) score on admission was E3M5V4. Radiology Imaging finding a foreign body in Left Frontal Lobe. Discussion : Wooden Penetrating Brain Injury was Nonmissile penetrating head injuries (NPHIs). The pathophysiology is similar to closed head injuries causing cerebral contusion or intracranial hemorrhage, but there is more chance of infection. Primary survey and stabilization of the patient with regard to the airway, breathing, cervical spine, and circulation including external hemorrhage. Computed tomography (CT) scanning of the head is primary modality . MRI can be a useful neuroradiologic modality if a penetrating object is a wood. Patient was performed Craniectomy Debridement and was treated with triple antibiotic regiment. Conclusion : The management of PBI differs considerably from nonpenetrating brain injury because of the unique mechanism of injury and pathophysiology involved in this type of trauma In this patient surgical treatment was undergoing after 12 h. Patient was treated with triple antibiotic regiment and was discharged on 7th day post operation. The recovery of the patient went uneventfull. Patient gained back his conciousness without any neurological deficit. Key words : Penetrating Brain Injury, Nonmissile, Wooden stick